Modeling Age-Associated Neurodegenerative Diseases in Caenorhabditis elegans - Palikaras, K.; Tavernarakis, N. (J Vis Exp, 2020)
Battling human neurodegenerative pathologies and managing their pervasive socioeconomic impact is becoming a global priority. Notwithstanding their detrimental effects on the human life quality and the healthcare system, the majority of human neurodegenerative disorders still remain incurable and non-preventable. Therefore, the development of novel therapeutic interventions against such maladies is becoming a pressing urgency. Age-associated deterioration of neuronal circuits and function is evolutionarily conserved in organisms as diverse as the lowly worm Caenorhabditis elegans and humans, signifying similarities in the underlying cellular and molecular mechanisms. C. elegans is a highly malleable genetic model, which offers a well-characterized nervous system, body transparency and a diverse repertoire of genetic and imaging techniques to assess neuronal activity and quality control during ageing. Here, we introduce and describe methodologies utilizing some versatile nematode models, including hyperactivated ion channel-induced necrosis (e.g., deg-3(d) and mec-4(d)) and protein aggregate (e.g., alpha-syunclein and poly-glutamate)-induced neurotoxicity, to monitor and dissect the cellular and molecular underpinnings of age-related neuronal breakdown. A combination of these animal neurodegeneration models, together with genetic and pharmacological screens for cell death modulators will lead to an unprecedented understanding of age-related breakdown of neuronal function and will provide critical insights with broad relevance to human health and quality of life.
Keywords: *Caenorhabditis elegans; *Disease Models, Animal; Aging/*metabolism/*pathology; Animals; Cell death; Humans; Ion Channels/metabolism; Necrosis; Neurodegenerative Diseases/*metabolism/*pathology/physiopathology; Neurons/metabolism/pathology; Quality of Life